Complete mitochondrial genome sequence of Arboreal Brown-toothed Shrew, Episoriculus macrurus. Issue 1 (1st January 2016) - Li, Bo; Song, Xuhao; Yan, Chaochao; Ran, Jianghong; Zhang, Xiuyue; Yue, Bisong
Abstract: The Arboreal Brown-toothed Shrew ( Episoriculus macrurus ) belongs to the family Soricidae, and distributes in China, Nepal, India, Myanma, and Vietnam. In this study, the complete mitochondrial genome sequence of E. macrurus was determined. The mitogenome is 16, 943 bp in length. Phylogenetic trees were constructed by the methods of Bayesian inference and maximum likelihood. The results showed that in the family of Soricidae, Crocidurinae differentiated earlier than Soricinae. Episoriculus was more close to Nectogale or Neomys rather than Sorex, and Blarinella was close to Sorex . This study contributes to illuminating the taxonomic status of E. macrurus .